Spermatogenesis, Spermatophore, and Seminal Fluid Production in the Adult Blue Crab Callinestes danae (Portunidae) - Zara, Fernando J. (2012)
Sperm and spermatophore production in Callinectes danae Smith, 1869 were examined by histochemistry and correlated with gonadosomatic (GSI) and hepatosomatic (HSI) indices. The GSI from developing (DE) and mature (MAT) males increased while the HSI decreased from DE to MAT, demonstrating that the maturation of the male reproductive system requires resources from the hepatopancreas. No histological or histochemical differences were observed between DE and MAT except for the larger amount of secretions produced in MAT. Spermatogenesis occurs in the seminiferous lobules surrounded by accessory cells. Each lobule is filled with cells at the same developmental stage. Spermatid maturation is characterized by an increase in the metachromatic acrosome. Sperm are released into seminiferous ducts, which moves them to the vas deferens divided into anterior (AVD), median (MVD), and posterior (PVD) regions. Spermatophore formation begins at the anterior part of AVD; sperm masses are separated and compacted in small packets by a basophilic and alcianophilic secretion. Small amounts of eosinophilic secretion, positive for proteins and neutral polysaccharides, are added around the sperm initiating the formation of the spermatophore wall. Mature round spermatophores are found in the posterior part of AVD and present a thick glycoproteinaceous wall, surrounded by acidic polysaccharides. The spermatophores are stored in MVD without size difference from DE to MAT. The MVD is filled with a granular secretion composed of glycoproteins. The secretion in PVD is fluid and homogeneous, facilitating the transference of the spermatophores. In conclusion, the hepatopancreas is related to the maturation of the male reproductive system in C. danae. DE males presented all histological conditions to fertilize females as MAT males, but the decrease in HSI and increase in GSI indices correlated with the vas deferens indicate that reserves are necessary to produce large amounts of seminal fluid in MAT males.